The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1161/01.str.27.9.1487
|View full text |Cite
|
Sign up to set email alerts
|

Declining Incidence and Mortality Rates of Stroke in Finland From 1972 to 1991

Abstract: The decline in the stroke incidence rate during the 1970s stabilized during the late 1980s and early 1990s; however, the case-fatality rate is still decreasing. Their combined effects may explain the continuing decline in stroke mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
68
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 12 publications
12
68
1
2
Order By: Relevance
“…This increase with advancing age has been observed in many studies. 5,16 Our study also showed a male preponderance among stroke patients. Other studies have demonstrated the increase is generally greater in males below 65 years of age than females in the same age group, but equalises with increasing age.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This increase with advancing age has been observed in many studies. 5,16 Our study also showed a male preponderance among stroke patients. Other studies have demonstrated the increase is generally greater in males below 65 years of age than females in the same age group, but equalises with increasing age.…”
Section: Discussionsupporting
confidence: 65%
“…16,17 An increase in the cases of stroke was observed with increasing age in our study but after 80 yrs the prevalence decreased probably due to a lesser number of at-risk population after 80 years or due to mortality. This increase with advancing age has been observed in many studies.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…There have been many studies on the incidence of aneurysmal subarachnoid hemorrhage(SAH) with widely varying annual incidences 2,3,6,[8][9][10][11][12] . The overall incidence of SAH was approximately 10 to 11 cases per 100,000 persons per year but varies significantly by region, with doubled rates in Japan and Finland and far lower rates in South and Central America 3,[8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%